Experimental Study on the Shape-Velocity Relationship of an Ellipsoidal Bubble in Inorganic Salt Solutions - Maldonado-Saavedra, M (2014)
Individual bubbles ca. 2.3 mm in diameter were produced at a capillary in water containing an inorganic salt (NaClO4, KCl, NaCl, Na 2SO4, or CaCl2). Using high speed photography and image analysis techniques, bubble aspect ratio and rise velocity were measured at 1 ms time intervals over a distance ca. 1.15-1.20 m above the capillary. All conditions showed oscillations in bubble aspect ratio and velocity that were related. Increasing concentration, on average, created more spherical bubbles that rose at lower velocities. The same observations were made in the presence of MIBC frother. Results suggest a unique relationship between bubble shape and rise velocity independent of solute type. The effect of inorganic salts on bubble behavior and gas dispersion in flotation systems is discussed. © 2013 Elsevier Ltd. All rights reserved.